Estrogen Receptor and Claudin-6 Might Play Vital Roles for Long-Term Prognosis in Patients With Luminal A Breast Cancer Who Underwent Neoadjuvant Chemotherapy - Liu, Yushi; Kang, Ye; Li, Jianyi; Zhang, Yang; Jia, Shi; Sun, Qiang; Ma, Yan; Zhang, Jing; Wang, Zhenrong; Cao, Yanan; Shen, Yang (Frontiers in Oncology, 2022)
Abstract: (1) Purpose: It is well-known that the pathological complete response (pCR) rate in patients with luminal A cancer (LAC) is lower than other subtypes of breast cancer. The Phenotype of cancer often alters after neo-adjuvant chemotherapy (NAC) which may be related to hypoxia, and the latter might induce the drift of Estrogen Receptor (ER). The phenotype drift in local advanced LAC after NAC might influence the long-term prognosis. (2) Methods: The oxygen concentration of cancer tissues during NAC were recorded and analyzed (n=43). The expression of ER and claudin-6 was detected in pre- and post-NAC specimens. (3) Results: NAC might induce the cycling intracanceral hypoxia, and the pattern was related to NAC response. The median follow-up time was 61 months. Most of patients (67%) with stable or increased ER and claudin-6 expression exhibited perfect prognosis (DFS=100%, 61 month). About 20% patients with decreased claudin-6 would undergo the poor prognosis (DFS=22.2%, 61 month). The contrasting prognosis (100% vs 22.2%) had nothing to do with the response of NAC in the above patients. Only 13% patients with stable claudin-6 and decreased ER, whose prognosis might relate to the response of NAC. (4) Conclusion: NAC might induce cycling intracanceral hypoxia to promote the phenotype drift in local advanced LAC, and the changes of ER and claudin-6 after NAC would determine long-term prognosis.